Can servant leaders fuel the leadership fire? The relationship between servant leadership and followers' leadership avoidance - Martin Lacroix; Armin Pircher Verdorfer (Administrative Sciences, 2017)
This study tested the effect of servant leadership on followers' inclinations to strive for and, in contrast, to avoid leadership responsibility. Results from a study in the health care context, including two waves of data from 222 employees, revealed that servant leadership had a small but positive effect on followers' leadership avoidance. This effect was influenced by followers' implicit conception of an ideal leader. Specifically, servant leadership was found to reduce leadership avoidance when the congruence with the followers' ideal leader prototype was high. Furthermore, followers' core self-evaluations and affective motivation to lead mediated the relationship between servant leadership and reduced leadership avoidance. Implications of these patterns for theory and practice and avenues for future research are discussed.
Keywords: 350; servant leadership; leadership avoidance; motivation to lead; core self-evaluations